3D- and 2D-QSAR models’ study and molecular docking of novel nitrogen-mustard compounds for osteosarcoma - Zhuo, Wenkun; Lian, Zheng; Bai, Wenzhe; Chen, Yanrong; Xia, Huanling (Frontiers in Molecular Biosciences, 2023)
Background: Dipeptide alkylated nitrogen mustard compound is a new kind of nitrogen mustard derivative, which has strong anti-tumor activity and can be used as a potential anti-osteosarcoma chemotherapy drug. Objective: 2D and 3D-QSAR models were established to predict the antitumor activity of dipeptide alkylated nitrogen mustard compounds. Method: In this study, linear model was established using heuristic method and nonlinear model was established using GEP algorithm, but 2D model had more limitations, so 3D-QSAR model was introduced and COMSIA method was used to establish 3D-QSAR model. Finally, a series of new dipeptide alkylated nitrogen mustard compounds were redesigned using 3D-QSAR model, and the docking experiments were carried out on several compounds with the highest activity against tumor. Result: The two- and three-dimensional QSAR models obtained in this experiment were satisfactory. A linear model with six descriptors was obtained in this experiment using the HM method in CODESSA software, where the descriptor 'Min electroph react index for a C atom' has the greatest effect on the compound activity; a reliable nonlinear was obtained using the GEP algorithm model (the best model was generated in the 89th generation cycle, with correlation coefficients of 0.95 and 0.87 for the training and test sets, respectively, and mean errors of 0.02 and 0.06, respectively); finally, 200 new compounds were designed by combining the contour plots of the CoMSIA model with each other and the descriptors in 2D-QSAR, among which compound I1.10 had high antitumor activity and docking ability.Conclusion: The model established in this study revealed the factors influencing the antitumor activity of dipeptide alkylated nitrogen thaliana compounds, and provided direction and guidance for the further design of efficient chemotherapy drugs for osteosarcoma.